2021
DOI: 10.20473/pmnj.v7i1.20431
|View full text |Cite
|
Sign up to set email alerts
|

Self-Structured Breast Cancer Awareness among Female Adolescent

Abstract: Introduction:The incidence of breast cancer has increased every year, mostly in developing countries. However, breast cancer awareness in women is still insufficient. A woman must be aware of breast cancer disease earlier. This study aimed to describe breast cancer awareness in female adolescents.Methods: The research design was used descriptive-analytic. The study population consisted of female adolescents in 10th-11th grade at Vocational High School in Surabaya, East Java, Indonesia. The sample was taken usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Therefore, adolescent girls represent an important target group for breast cancer education and development of awareness. 3,10 When examining studies conducted in Türkiye on this topic, it is observed that these studies primarily focus on women aged 18 and older, utilizing descriptive designs to depict the existing situation. The purpose of this study is to enhance breast cancer awareness among adolescent girls through an educational program based on the HBM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adolescent girls represent an important target group for breast cancer education and development of awareness. 3,10 When examining studies conducted in Türkiye on this topic, it is observed that these studies primarily focus on women aged 18 and older, utilizing descriptive designs to depict the existing situation. The purpose of this study is to enhance breast cancer awareness among adolescent girls through an educational program based on the HBM.…”
Section: Introductionmentioning
confidence: 99%
“…Kesadaran tentang kanker payudara perlu ditingkatkan tidak hanya pada perempuan dewasa, tetapi juga pada perempuan remaja (Pangestuti et al, 2021). Menurut Yayasan Kanker Payudara Indonesia ada kecenderungan penurunan usia penderita kanker payudara di Indonesia terutama pada remaja.…”
unclassified